"Of course we care!": A qualitative exploration of Australian livestock producers' understandings of farm animal welfare issues. (April 2021) - Buddle, Emily A.; Bray, Heather J.; Ankeny, Rachel A.
Abstract: The welfare of farm animals is increasingly of concern to meat producers as well as consumers and the broader community; however these groups conceptualize animal welfare in different ways, which is likely to present a barrier to effective communication and resolution of conflicts between these groups particularly as livestock producers face increasing scrutiny by community members. Since most research to date on producer understandings of animal welfare has been based in Europe and North America, we used qualitative methods to examine producers' understandings of animal welfare in the red-meat (beef and sheep-meat) sectors in Australia. Through the use of interviews, we found that Australian producers linked "good welfare" with productivity and profitability and were willing to adopt new practices to improve animal welfare. Producers were concerned about negative public perceptions of their industry and suggested that education was needed to correct misinformation about the industry. Australian producers place significant emphasis on the relationship between climatic conditions and farm animal welfare, often describing their attempts to do the best they can in periods of adverse weather, a significant finding as awareness of climate change and its effects continues to increase. Our findings contribute to a broader effort to identify shared values between different stakeholder groups (i.e. producers, consumers, and the broader community) to highlight areas of commonality between these groups and provide more effective pathways for improving conversations about how to produce meat humanely and how animal welfare practices can continue to evolve and improve. Highlights: Australian livestock producers link "good welfare" with productivity and profitability. Australian sheep and beef cattle producers are willing to adopt new practices to improve animal welfare. Negative public perceptions of the sheep and beef cattle industry in Australia were of concern for producers. Australian producers place significant emphasis on the relationship between climatic conditions and farm animal welfare. This research helps to identify shared values between different stakeholder groups (i.e. producers and the broader community). This research can be used to highlight ways to improve conversations about how animal welfare practices can continue to evolve.